The 2dF galaxy redshift survey: Wiener reconstruction of the cosmic web - Erdoǧdu, P; Lahav, O; Zaroubi, S; Efstathiou, G; Moody, S; Peacock, J; Colless, M; Baldry, I; Baugh, C; Bland-Hawthorn, J; Bridges, T; Cannon, R; et al. (2004)
We reconstruct the underlying density field of the Two-degree Field Galaxy Redshift Survey (2dFGRS) for the redshift range 0.035 < z < 0.200 using the Wiener filtering method. The Wiener filter suppresses shot noise and accounts for selection and incompleteness effects. The method relies on prior knowledge of the 2dF power spectrum of fluctuations and the combination of matter density and bias parameters, however the results are only slightly affected by changes to these parameters. We present maps of the density field. We use a variable smoothing technique with two different effective resolutions: 5 and 10 h -1 Mpc at the median redshift of the survey. We identify all major superclusters and voids in the survey. In particular, we find two large superclusters and two large local voids. The full set of colour maps can be viewed on the World Wide Web at http://www.ast.cam.ac.uk/~pirin.